A state-of-the-art review of factors that predict mortality among traumatic injury patients following a road traffic crash. (March 2022) - Alharbi, Rayan Jafnan; Lewis, Virginia; Miller, Charne
Abstract: Background: Traffic related injuries are a major public health problem worldwide with millions of people dying every year. The objective of this state-of-the-art review was to identify the factors reported in the literature as being associated with mortality for trauma patients following road traffic crashes. Method: A systematic search was undertaken of PubMed/MEDLINE, EMBASE, CINAHL, Web of Science, and Cochrane Library databases to identify articles published in the past two decades (2000–2020). Of 8257 records, 4507 remained for title, abstract and full text screening after duplicates were removed. The level of evidence of selected studies was assessed using The National Health and Medical Research Council (NHMRC) guideline. Results: This review included eighty primary research studies examining mortality risk factors following a road traffic crash. The study identified factors in five categories; (i) demographic factors; (ii) behavioural factors; (iii) crash characteristics; (iv) environmental and timing factors; (v) injury severity and pre-injury/condition. The primary studies are summarised in a matrix. Included studies included level II to level IV levels of evidence based on the NHMRC criteria. Conclusion: This study shows that there are a large number of factors associated with increased risk of mortality following diverse types of traffic crashes. Understanding these wide-ranging factors can strengthen injury and mortality prevention by guiding decision makers about where to focus strategy implementation.